A study of multi-party system in Tuva - Malyutina, Larisa F. (The New Research of Tuva, 2015)
Article is a review to monography by Z.Yu Dorzhu and O.P.Oyun “Multi-party system in Tuva: genesis and formation” (1990’s and early 21st century) (Kyzyl, TuvSU, 2015. 258 P.). The monography estimates the works of Tuvan scientists, who analyzed the process of formation of multi-party system in Tuva.
Keywords: Tuva; ethnopolitology of Tuva; history of politics; political party; history of Tuva; review